State’s Obligation to Gender Equality: The case of women’s right to ancestral property in Bangladesh - Alam, Nadira Binta (Dhaka University Law Journal, 2025)
The extent and depth of States’ obligations concerning women’s equal property (ancestral) rights are the cornerstone of this article. Analysing the two most important treaties, i.e. the International Convention of Economic, Social and Cultural Rights (ICESCR), and the International Convention on The Elimination of All Forms of Discrimination against Women (Women’s Convention) to which Bangladesh is a party allows the author to focus on concerns such as non- discrimination and equality with regards to property rights. Subsequently, personal law governing women’s inheritance rights in Bangladesh and national legislation will be evaluated to determine if they comply with the state’s international human rights obligations. This article also resolves to understand the feasibility of bringing legislative reforms to the personal laws in a way that guarantees women’s equal right to inheritance, following the right to property standards incorporated in international human rights treaties, without impairing the core values of the religion and the society. Dhaka University Law Journal, 2025, 36 (1), 209-233